Seismic hazard assessment at micro level in Gandhinagar (the capital of Gujarat, India) considering soil effects. Issue 109 (June 2018) - Mohan, Kapil; Rastogi, B.K.; Pancholi, Vasu; Gandhi, Drasti
Abstract: Gandhinagar City (the Capital of Gujarat, India) falls under Zone III on the seismic zoning map of India where an earthquake of magnitude 6 can be expected. It is a well established fact that the site amplification/ shaking and damage is large in soil covered areas. To estimate the effect of soil on ground motion and to estimate the strong ground motion parameters at surface, soil modeling and the ground response analysis have been conducted along uniformly distributed 14 boreholes drilled upto a depth of 50 m. The methodology is divided into three parts (i) Estimation of depth of Engineering Bed layer (EBL) (a layer with a shear wave velocity 400 m/s ≤ Vs ≤ 750 m/s, N value >80 and minimum soil variation below it) through soil modeling, (ii) Estimation of Ground Motion at EBL due to scenario earthquake at nearby active fault and (iii) Estimation of surface strong ground motion using 1D ground response analysis through SHAKE 2000 program. The EBL is found at a depth of 21–33 m (shallower in central part and deeper in northern and southern parts). The Near-Field scenario earthquake (Eq.) of magnitude Mw 6.0 has been considered along East Cambay Fault (normal fault, 60° dip) located at about 20 km east and Far Field scenario Eq. of Mw 7.6 is considered along Kachchh Mainland Fault located 270 km west. The Peak Ground acceleration (PGA) of 0.172–0.237 g have been estimated at surface due to near field earthquake scenario. The mean spectral acceleration maps for 0.1–0.4 s, 0.4–0.7 s, 0.7–1.0 s and 1.0–1.5 s have also been computed. The mean spectral acceleration for the period of 0.1–0.4 s has been varying from 0.330 g to 0.508 g, for period of 0.4–0.7 Sec, it has been varying from 0.151 g to 0.161 g and for period between 1.0 and 1.5 Sec, it has been found from 0.83 g to 0.09 g. The PGA is found increased by 5–38% in the first subsurface soil layer in Gandhinagar city. The PGA of the order of 0.059–0.072 g and peak Spectral acceleration of the order of 0.187–0.259 g have been computed (with predominant periods of 0.1 s and 0.31 s) due to Far-Field Eq. scenario and are found less than Indian code. The PGA and Spectral acceleration (Sa) values are found higher than the Indian code in the period range of 0.1–0.4 s (one to four storey buildings) for Near Field Eq. Scenario. Highlights: Geotechnical investigation has been carried out at fourteen boreholes. The soil modeling has been conducted using Soil Type, N value and Shear wave velocity. The near field and far field earthquake scenarios are considered. Ground response analysis has been conducted using both scenario earthquakes. Seismic Hazard analysis is presented in Gandhinagar (Gujarat).